Multicenter Comparison of 18F-FDG and 68Ga-DOTA-Peptide PET/CT for Pulmonary Carcinoid. (March 2015) - Lococo, Filippo; Perotti, Germano; Cardillo, Giuseppe; De Waure, Chiara; Filice, Angelina; Graziano, Paolo; Rossi, Giulio; Sgarbi, Giorgio; Stefanelli, Antonella; Giordano, Alessandro; Granone, Pierluigi; Rindi, Guido; et al.
Abstract : Purpose: The aims of this study were to retrospectively evaluate and compare the detection rate (DR) of 68 Ga-DOTA-peptide and 18 F-FDG PET/CT in the preoperative workup of patients with pulmonary carcinoid (PC) and to assess the utility of various functional indices obtained with the 2 tracers in predicting the histological characterization of PC, that is, typical versus atypical. Methods: Thirty-three consecutive patients with confirmed PC referred for 18 F-FDG and 68 Ga-DOTA-peptide PET/CT in 2 centers between January 2009 and April 2013 were included. The semiquantitative evaluation included the SUVmax, the SUV of the tumor relative to the maximal liver uptake for 18 F-FDG (SUVT/L ) or the maximal spleen uptake for 68 Ga-DOTA-peptides (SUVT/S ), the ratio between SUVmax of 68 Ga-DOTA-peptides PET/CT, and the SUVmax of 18 F-FDG PET/CT (SUVmax ratio). Histology was used as reference standard. Results: Definitive diagnosis consisted of 23 typical carcinoids (TCs) and 10 atypical carcinoids. 18 F-FDG PET/CT was positive in 18 cases and negative in 15 (55% DR). 68 Ga-DOTA-peptide PET/CT was positive in 26 cases and negative in 7 (79% DR). In the subgroup analysis, 68 Ga-DOTA-peptide PET/CT was superior in detecting TC (91% DR; P < 0.001), whereas 18 F-FDG PET/CT was superior in detecting atypical carcinoid (100% DR; P = 0.04). The SUVmax ratio was the most accurate semiquantitative index in identifying TC. Conclusions: Overall diagnostic performance of PET/CT in detecting PC is optimal when integrating 18 F-FDG and 68 Ga-DOTA-peptide PET/CT findings. In the subgroup analysis, the SUVmax ratio seems to be the most accurate index in predicting TC. Both methods should be performed when PC is suspected or when the histological subtype is undefined.